Information architectures : designing integrated social information systems/databases for the Caribbean - Busby, Lancelot A. (s.n.] [S.l.)
Looks at what is an information architecture and how it differs from the information organization in any of the Caribbean countries. Focuses on the design and maintenance of the arechitecture required for monitoring social development. Discusses the nature of an indicator as opposed to a direct measure of a phenomenon and the properties of a good indicator. Examines a number of indicators suggested by UNICEF and comments on them in terms of their apparent relevance, priority and likelihood of efficiency. Looks at the information sources from which indicators are commonly being developed and suggests new ones. Discusses how the monitoring through indicators will be operationalized and normalized with other data sets with which it can be analyzed, both within any organization and with the data sets of other organizations.